Strategic capacity and investment road 0AP planning - Kumar,S; McGinty,J (2018)
An effective methodology for the strategic capacity and investment planning roadmap development was successfully deployed at several steel plants. There are a number of key issues that need to be considered in the development of the roadmap some of these include product mix, production scheduling, plant design / layout / logistics, operating practice, metallurgical aspects, environmental, discipline engineering, project / construction management, as well as financial viability analysis and risk assessment. Depending on the requirement of the steel plant, strategic roadmaps can be developed for individual process areas, the total melt shop or the entire steel works covering all processes (ironmaking, steelmaking and rolling / finishing). The objective of developing these strategic roadmaps is to determine / derive the best possible holistic solutions at early phases of the capital expansion projects to attain the corporate targets of key performance indicators (KPIs) with minimal capital investment, improved operating practices / procedures and lower operating costs.